Relationship of Social Capital, Entrepreneurial Competence, and Performance: The Case of Convection SMEs - Sutikno, Sutikno; Fikriyah, Minkhatul; Nurkhin, Ahmad (Economic Education Analysis Journal, 2022)
This study aimed to examine the relationship of social capital, entrepreneurial competence, and company performance on Convection SMEs in Pemalang. The purpose of this study was also to examine the mediating role of entrepreneurial competence on the effect of social capital on MSME performance. This study was a quantitative study with population of convection SMEs in Ulujami District, Pemalang Regency. This study obtained 285 MSME business owners as research respondents. The data collection method used the questionnaire. Methods of descriptive analysis and path analysis were used to analyze the data of this study. The study results indicated a significant effect of social capital and entrepreneurial competence on the MSMEs performance. Entrepreneurial competence had been shown to significantly mediate the effect of social capital on the MSMEs performance. Social capital must be maintained and enhanced through the ability of MSME owners and managers in establishing relationships with partners, customers, and policy makers. Good social capital will encourage the entrepreneurial competence of MSME owners and managers to be stronger because they get information, experience, and assistance from various related parties.